Outsourcing Versus Insourcing Sumber Daya Manusia Pengaruhnya terhadap Kinerja pada Industri Manufaktur BUMN - Sudarso, Indung (Jurnal Aplikasi Manajemen, 2008)
This research aimed to: (1) analyze the difference of human resources outsourcing and insourcing regarded as from performance, competence, personality, commitment, and motivation empiricall, (2) analyze the effect of competence, personality, commitment, and motivation on performance of human resources outsourcing and insourcing. Research obyect selected is public ownership (BUMN) manufacturing industry which pertained as big industry, and has produced heavy equipments or transportation in Indonesia. The companies are: PT PAL Indonesia, producer of ship, PT Barata Indonesia, producer of heavy equipment, and PT. INKA producer of train. The research design was conducted by using causality analysis with quantitative approach and also survey methodology. The population in this study is employees at three companies which is amount to 8.726 peoples. Especially for operational and production level is counted 3.140 peoples. The samples wich has been circularized amounts to 400 respondents and which can be analyzed counted 284 respondents. Using Structural Equation Modeling (SEM) and discriminant analysis. The results of discriminant analysis shows that any difference between human resources outsourcing and insourcing, where the outsourcers has bigger motivation and competence than insourcing. While another variables, such as personality and commitment has no differences. And then, the results of SEM indicates that the four variables (competence, personality, commitment, and motivation) has no significant effect on human resorces outsourcing performance. Research suggestion for improving performance of human resources outsourcing is by doing job contract revision between management and outsourcing employess about earnings which can be accommodate the incentive system.